A novel S-sulfhydrated human serum albumin preparation suppresses melanin synthesis - Ikeda, M.; Ishima, Y.; Kinoshita, R.; Chuang, Victor; Tasaka, N.; Matsuo, N.; Watanabe, H.; Shimizu, T.; Ishida, T.; Otagiri, M.; Maruyama, T. (Elsevier BV, 2018)
Products of ultraviolet (UV) irradiation such as reactive oxygen species (ROS) and nitric oxide (NO) stimulate melanin synthesis. Reactive sulfur species (RSS) have been shown to have strong ROS and NO scavenging effects. However, the instability and low retention of RSS limit their use as inhibitors of melanin synthesis. The free thiol at Cys34 on human serum albumin (HSA) is highly stable, has a long retention and possess a high reactivity for RSS. We report herein on the developm ent of an HSA based RSS delivery system. Sulfane sulfur derivatives released from sodium polysulfides (Na 2 S n ) react readily with HSA. An assay for estimating the elimination of sulfide from polysulfide showed that almost all of the sulfur released from Na 2 S n bound to HSA. The Na 2 S n -treated HSA was found to efficiently scavenge ROS and NO produced from chemical reagents. The Na 2 S n -treated HSA was also found to inhibit melanin synthesis in B16 melanoma cells and this inhibition was independent of the number of added sulfur atoms. In B16 melanoma cells, the Na 2 S n -treated HSA also inhibited the levels of ROS and NO induced by UV radiation. Finally, the Na 2 S n -treated HSA inhibited melanin synthesis from L-DOPA and mushroom tyrosinase and suppressed the extent of aggregation of melanin pigments. These data suggest that Na 2 S n -treated HSA inhibits tyrosinase activity for melanin synthesis via two pathways; by directly inhibiting ROS signaling and by scavenging NO. These findings indicate that Na 2 S n -treated HSA has potential to be an attractive and effective candidate for use as a skin whitening agent.